Mercado de Carbono: Proposta de Implementação em um Município do Ceará. - Oliveira, Jônatas José Lôbo (2024)
With globalization, mitigating the effects of climate change has become increasingly emerging. Currently with the Paris Agreement, countries understand the relevance of financial incentives and the need for investment to drive the necessary adjustments and retain the changes caused by excess Greenhouse Gases, popularly known as the Carbon Market. In this sense, the present study seeks to propose guidelines for an action plan to use the carbon market in Ceará as a public policy for sustainable development. Through the identification of similar initiatives, as well as understanding the economic, social and environmental profile, both in Ceará and the municipality of Caucaia, interconnected with the emissions profile. With the data collected, the main actors involved were analyzed, as well as the main climate risks that the municipality is susceptible to, as well as local characteristics, emission patterns and potential mitigation projects to contemplate an integrated action. The result was the verification of the feasibility of an action plan outlined targeting key sectors for intervention, communication processes for dialogue between different actors and sectors, implementation of renewable energy projects, reforestation, environmental awareness programs and tax incentives for practices sustainable. In addition to identifying relevant points for verification, such as governance issues, technical training and infrastructure, as well as opportunities associated with the transition to a lowcarbon economy. Finally, guidelines are presented that focus on reliable governance structures, based on the implementation of projects that achieve beneficial impacts on the environment, the social and the economic, with communication, transparency and governance as bases.